Resilience and Adaptability in Paracetamol Supply Chains: A Systems Perspective on COVID-19 Challenges and Responses in Ethiopia - Tsegaye Melaku; Zeleke Mekonnen; Gudina Terefe Tucho; Joe Viana; Christine Årdal; Marianne Jahre (Logistics, 2025)
Background: The COVID-19 pandemic exposed vulnerabilities in global supply chains, including those for essential medicines like paracetamol. This study aimed to assess the resilience and adaptability of Ethiopia’s paracetamol supply chain during the pandemic. Methods: A mixed-methods approach was employed, combining semi-structured interviews with key stakeholders and analysis of secondary data on paracetamol availability and supply chain disruptions. The study employed systems thinking and supply chain resilience frameworks, utilizing causal loop diagrams to visualize system dynamics. Results: Eighteen stakeholders, representing seven pharmaceutical manufacturers, five import companies, and five wholesalers, participated in the study. These participants had between three and fourteen years of experience in their respective roles. The study revealed complex interactions within the paracetamol supply chain, highlighting both challenges and adaptive responses. While 500 mg paracetamol tablets were readily available, shortages of other formulations were observed due to a range of factors, including limited product diversification, political instability, inflation, and reduced production efficiency. Conclusions: The resilience and adaptability of stakeholders, particularly manufacturers and importers, were crucial in maintaining the supply of 500 mg paracetamol tablets. Key strategies included regional sourcing, increased production, and improved partnerships. Understanding the interconnectedness of factors within the supply chain is essential for developing effective strategies to enhance its resilience and ensure sustained access to paracetamol in the future.